Self-care behavior among adult patients with hypertension in Padang, West Sumatra, Indonesia: A cross-sectional study - Rika Sarfika; Sulistiawati; Esi Afriyanti; I Made Moh. Yanuar Saifudin (Belitung Raya Foundation, Indonesia, 2023)
Background: Self-care behavior is crucial in preventing chronic diseases, such as hypertension, which has become highly prevalent in Indonesia. Hypertension, often referred to as the “silent killer” due to its asymptomatic nature, can easily go unnoticed. Neglecting its treatment can lead to severe complications, including heart disease, heart failure, and stroke. Despite adults with hypertension feeling well, embracing self-care behavior, including making healthy lifestyle choices, disease management, and enhancing life quality, remains essential. Objective: This study aimed to describe the self-care behavior of adult patients with hypertension in Indonesia. Methods: A cross-sectional study design was employed, involving 270 participants selected through consecutive sampling. Data were collected between 15 March and 4 April 2023, using the Hypertension Blood Pressure Self Care Profile (HBP-SCP) questionnaire in six public healthcare centers in Padang City, West Sumatra, Indonesia. The data were analyzed using descriptive analysis, Mann-Whitney, and Kruskal-Wallis tests. Results: The self-care behavior among adult patients with hypertension was at a moderate level (Mean = 49.78, SD = 6.64), and it had significant differences according to ethnicity (p = 0.041), marital status (p = 0.017), and body mass index (p = 0.008). Conclusion: The findings highlight the influence of diverse ethnic backgrounds, various marital statuses, and differing body mass index levels, which may lead to distinct approaches to managing hypertension. These results offer valuable insights for nurses and other healthcare professionals to develop comprehensive strategies to enhance self-care among adult patients with hypertension.